Bioresponsive hydrogel scaffolding systems for 3D constructions in tissue engineering and regenerative medicine. (April 2013) - Lau, Ting Ting; Wang, Dong-An
Among the diversity of scaffolding systems available, hydrogel remains a popular choice for tissue engineering applications. The current state-of-the-art bioresponsive hydrogels demand intricate designs in pursuit of acquiring desired timely responses, such as controlled release of biological factors, changes in mechanical properties and scaffold degradation, at the same rate as the natural extracellular matrix. In this review, a variety of bioresponsive hydrogels are discussed; in particular, bioactive and biodegradable hydrogels that facilitate cellular development and tissue morphogenesis are highlighted. Bioactive hydrogels are designed to deliver biomolecules such as cell-adhesive moieties and instructive ligands at close proximity to the cell for better uptake or exposure. Biodegradable hydrogels provide transient scaffolding support for therapeutic cell settlement while gradually degrading in response to physical or enzymatic stimuli. In addition, biomechanical stimuli from hydrogels can induce mutual constructive responses on cells and, hence, will also be covered in this review.